1988
DOI: 10.1172/jci113706
|View full text |Cite
|
Sign up to set email alerts
|

Cycle length dependence of human action potential duration in vivo. Effects of single extrastimuli, sudden sustained rate acceleration and deceleration, and different steady-state frequencies.

Abstract: Using a new method for long-term recording of monophasic action potentials from the human heart, we studied in 17 patients the effects on ventricular action potential duration (APD) of three clinically pertinent cycle length perturbations:(1) single extrastimuli, (2) abrupt sustained rate acceleration and deceleration, and (3) different steady-state cycle lengths. Results were: (a) APD after single extrastimuli at progressively longer cycle lengths were related to the extrastimulus cycle length with a biphasic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
256
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 426 publications
(296 citation statements)
references
References 36 publications
(50 reference statements)
36
256
4
Order By: Relevance
“…This is based on original work by Franz et al showing that adaptation to rate change approximates an asymptote by 2 minutes for a wide range of cycle length perturbations. 17 This is also the case for patients with atrial fibrillation as we ourselves confirmed in a more recent study. 18 The 30-second LV UEG recordings were analyzed off-line using a custom software script within MATLAB (MathWorks, Massachusetts, USA) to derive the ARI.…”
Section: Functional Remodeling Assessed By Transthoracic Echocardiogrsupporting
confidence: 72%
“…This is based on original work by Franz et al showing that adaptation to rate change approximates an asymptote by 2 minutes for a wide range of cycle length perturbations. 17 This is also the case for patients with atrial fibrillation as we ourselves confirmed in a more recent study. 18 The 30-second LV UEG recordings were analyzed off-line using a custom software script within MATLAB (MathWorks, Massachusetts, USA) to derive the ARI.…”
Section: Functional Remodeling Assessed By Transthoracic Echocardiogrsupporting
confidence: 72%
“…16 The latter was proposed to be modulated by catecholamines, where sympathetic Initial measurement (weeks) activation results in an acceleration of the rate-adaptation through stimulation of Na + -K + pumps. 17 The shortened QT/HR hysteresis lag observed during pregnancy might therefore be caused by increased sympathetic outflow to the ventricles that normalized within 3 days postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…The initial adaptation (around 50%) of QT change occurs the order of a 50 to 60 s time frame, the terminal adaptation lasting above 2 min. 4,15,18 Less is known about QT hysteresis during physiologic HR fluctuation not associated with atrial pacing or acute exercise. In a recent study, Pueyo et al showed that the hysteresis phenomenon was different among subjects and was also influenced by amiodarone.…”
Section: Discussionmentioning
confidence: 99%
“…3 The main electrophysiologic property of ventricular repolarization is inversely related to heart rate (HR). 4,5 To compare QT intervals within and between subjects, numerous solutions have been proposed to take this phenomenon into account. The so-called "universal-correction" formulae have been shown to over-or undercorrect the QT interval potentially when HR changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation